Disability and participation in physical activity and non-elite sport environments: a critical investigation of persons with disabilities experiences - Brand, Dominique (Division of Disability Studies, 2023)
Sport is often praised for its capacity to alleviate social exclusion. However, for many persons with disabilities and people trapped within the poverty cycle, sport remains elusive in terms of accessible process and practice. To better understand sport's wider inclusionary and exclusionary outcomes this study explored experiences of persons with disabilities and the assumptions, distinctions and ideologies surrounding sport as a means for social inclusion. Saxton (2018) argues that we continue to hold a narrow understanding of the nature of participation for athletes with disabilities, especially non-elite athletes. Such participation often involves barriers and exclusion, denying persons with disabilities access to psychological and physiological benefits of participation. The position that sport has gained, and held, in development reflects an understanding that sport can be a steppingstone to upward social mobility, potentially providing a means for material advancement, increased social status and occupational prestige (Carrington, 1986; Hartmann & Kwauk, 2011; Spaaij, Magee, & Jeanes, 2014). My research acknowledges the influential role sport has gained in society, whether it be for the purposes of competition, enjoyment, or development (Eitzen, 2005). The significance of this exploratory study is to contribute to the gap in knowledge surrounding persons with disabilities' perspectives and experiences of sport and physical activity participation; this will add to the sports research knowledge base from a Global South perspective, nuanced with the diversity these environments provide. The study utilised a biographical narrative approach to investigate the diverse nature of non-elite sport participation by persons with disabilities. Emphasis was placed on understanding the variety of experiences of participants from diverse socio-economic and cultural backgrounds. The research has generated ten narratives of participants from Cape Town, South Africa, all of whom indicated that sport participation was fundamentally important in their lives. Although the interviewees identified with sport participation as a core value, they also showed how opportunities to play sport are not readily available to them. In sharing their lived experiences, their unique narratives contributed to the identification of a participation framework, which is part of the main findings of the study. Key findings of the study: The participation framework acknowledges how different societal responses to disability influence a person's experiences of participation, while providing a new language to facilitate an expanded understanding of how role-players within sport environments perpetuate exclusionary practices. Within non-elite sport environments there currently remain very limited options and opportunities for persons with disabilities. In the process of gaining access to participate, the distress of navigating material/non-material barriers means that persons with disabilities often pay a premium (psychoemotional cost) for the privilege of access, with its associated positive outcomes (achieving a sense of self or being able to recast one's identity). Passive inclusion occurs in organisations that assume they practice authentic inclusivity simply by virtue of having persons with disabilities present in their structures. This approach side-steps the more complex task of unpacking exclusionary practices; it pushes the responsibility back to persons with disabilities when all they want to do is participate in sport. When saddled with the task of understanding and addressing their own exclusion it is easy to see why some persons with disabilities may withdraw and demonstrate an instinctual need to self-protect against further oppressive treatment. As reflected in current critiques of the global sport for development agenda, persons with disabilities are still only represented on the periphery of programmes and research. The framework and language produced in this study can be the starting point to support future sport for development programmes by engaging with inclusivity through understanding exclusionary practices. The theoretical and methodological implications of the study urgently call on global role-players within sport and development to take responsibility for the role they have in perpetuating such practices. A drive towards quick results and efficiency rather than a focus on changing people's lives predominates in the development world. This approach is inflicted on the Global South by virtue of vulnerability created by our need for resources from the Global North. This study offers steps towards facilitating a conversation surrounding the experiences of persons with disabilities within sport environments and the implications of these for a collective agenda to create a more inclusive, transformed society.